The influence of geographic heterogeneity in predation pressure on sexual signal divergence in an Amazonian frog species complex. (26th November 2012) - Trillo, P. A.; Athanas, K. A.; Goldhill, D. H.; Hoke, K. L.; Funk, W. C.
Abstract: Sexual selection plays an important role in mating signal divergence, but geographic variation in ecological factors can also contribute to divergent signal evolution. We tested the hypothesis that geographic heterogeneity in predation causes divergent selection on advertisement call complexity within the Engystomops petersi (previously Physalaemus petersi ) frog species complex. We conducted predator phonotaxis experiments at two sites where female choice is consistent with call trait divergence. Engystomops at one site produces complex calls, whereas the closely related species at the other site produces simple calls. Bats approached complex calls more than simple calls at both sites, suggesting selection against complex calls. Moreover, bat predation pressure was greater at the site with simple calls, suggesting stronger selection against complex calls and potentially precluding evolution of complex calls at this site. Our results show that geographic variation in predation may play an important role in the evolution and maintenance of mating signal divergence.